Korelasi Sikap Ilmiah Dan Pemahaman Konsep Pada Materi Suhu Dan Perubahannya Pada Siswa Kelas VII SMP Negeri 1 Angkola Barat - Tohir Pardamean.; Sri Utami Kholilla Mora Siregar; Eni Sumanti Nasution (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to determine the correlation of scientific attitudes to understanding concepts in the Material of Temperature and Its Changes in Class VII Students of SMP Negeri 1 Angkola Barat for the 2023-2024 Academic Year. The formulation of the problem in the research conducted is whether there is a correlation between scientific attitudes towards understanding the concept on the Material of Temperature and Its Changes in Class VII Students of SMP Negeri 1 Angkola Barat for the 2023-2024 Academic Year?. This research method uses a type of quantitative research with a correlation research type. The sample used was 30 students at Class VII of SMP Negeri 1 Angkola Barat. The instrument used for scientific attitude using a questionnaire with a Likert scale and understanding of concepts is the result of student exams using temperature and its changes. Data analysis techniques using normality test, homogeneity test, linearity test. And test the hypothesis using the correlation test. The results showed that there was a relationship between scientific attitude and conceptual understanding of the material temperature and its changes in class VII students of SMP Negeri 1 Angkola Barat.